The International monetary system : choices for the future - Connolly, Michael B.; University of South Carolina (New York : Praeger, 1982)
This book highlights the importance and interdependence of the world's many different financial economic environments. It noted the issues that must be raised before a meaningful discussion of the proper financial system for the 1980s and beyond. Such as Exchange rates policies of developing countries; International monetary competition; Alternative monetary systems etc.
Papers from the Carolina Currency Conference on the Choice of an Exchange Rate System, held May 1-2, 1981 at the University of South Carolina, Columbia, S.C.
Includes bibliographies.
usc 10/04/2018
Loans
Keywords: Foreign exchange rates; International finance